Peran Dukungan Sosial Dan Communal Coping Dalam Proses Berduka Akibat Kehilangan Ibu Pada Dewasa Awal Suku Aceh: Studi Kasus Kualitatif - Rifqa Aulia Hafifuddin; Siti Hajar Sri Hidayati (Prodi Bimbingan dan Konseling Islam Fakultas Dawah dan Komunikasi UIN Ar-Raniry, 2026)
Abstract: Maternal loss during emerging adulthood can alter emotional security, family roles, and the transition toward independence. Previous bereavement studies have mainly examined social support as individual assistance, while studies of Acehnese death traditions have emphasized ritual solidarity; neither fully explains how support becomes a shared coping process in the personal experience of maternal loss. This study examined the roles of social support and communal coping in the acceptance of maternal loss among Acehnese emerging adults. A qualitative collective case study was conducted in Aceh from January to June 2021 through in-depth interviews with two participants, a 25-year-old man and a 23-year-old woman, who had lost their mothers approximately one year earlier. The findings showed that emotional, practical, informational, and spiritual support helped participants express grief, manage daily demands, understand fluctuating emotions, and develop religious meaning. Communal coping emerged through shared appraisal of loss as family and community concern and collaborative action involving relatives, neighbors, collective prayer, samadiah, religious gatherings, and assistance with mourning activities. Social support addressed needs, whereas communal coping transformed that support into collective involvement. Together, both processes helped participants live alongside grief, reorganize family roles, and maintain bonds with their mothers through memories, values, and prayer. Keywords: social support; communal coping; maternal loss; Aceh